(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article provides theoretical and practical information on the integration of artificial intelligence (AI) technology into educational processes and its significance in determining efficiency, including the use of platforms for individualizing educational processes, correcting the workload of teachers and improving the quality of education and obtaining educational resources, automatic guidance of student knowledge, and effective organization of distance learning. The article presents international experiences, impact, and scientific research on the development of technology in the role of artificial intelligence in education.